Spatially dispersed one-dimensional carbon architecture on oxide framework for oxygen electrochemistry - Devi, Hemam Rachna (2022)
The rational design of bifunctional electrocatalyst is important for sustainable energy storage and conversion devices such as metal-air batteries and fuel cells. Herein, we have designed a unique architecture where carbon nanotubes (CNTs) are supported on an oxide template. NiCo encapsulated N-doped carbon nanotubes were grown vertically outward from the nickel–cobalt oxide flowers for oxygen evolution reaction (OER) and oxygen reduction reaction (ORR). The hybrid shows enhanced water oxidation performance (321 mV at 10 mA/cm2) and decent ORR activity (E1/2 at 0.75 V vs RHE) due to better conductivity and a large electrochemical surface area. Enhanced OER activity can be ascribed to high Ni and Ni3+ content whereas improved ORR activity results from enhanced active nitrogen species (pyridinic, M−Nx and graphitic) and higher water contact angle (due to unique architecture). Further, reversible oxygen electrochemistry with Δ E = 0.80 V indicates its potential as a bifunctional electrocatalyst. The hybrid electrocatalyst has shown good operational stability and durability for OER and ORR. Finally, the practical feasibility as cathode catalyst for metal-air battery has been demonstrated by powering a light emitting diode.